Efficacy and safety of pasireotide-LAR for the treatment of refractory bleeding due to gastrointestinal angiodysplasias: results of the ANGIOPAS multicenter phase II noncomparative prospective double-blinded randomized study. (15th February 2018) - Benamouzig, Robert; Benallaoua, Mourad; Saurin, Jean-Christophe; Boubaya, Marouane; Cellier, Christophe; Laugier, René; Vincent, Magalie; Boustière, Christian; Gincul, Rodica; Samaha, Elia; Grandval, Philippe; Aparicio, Thomas; et al.
Background: Gastrointestinal angiodysplasias (GIADs) could be responsible for recurrent bleeding and severe anemia. Somatostatin analogs could reduce transfusion requirements in these patients but no randomized controlled study is available. The main objective of the ANGIOPAS phase II double-blinded randomized, noncomparative study was to assess the effectiveness of pasireotide-LAR in reducing transfusion requirements in patients with refractory GIADs bleeding. Methods: A total of 22 patients with transfusion requirements ⩾6 units of packed red blood cells (pRBCs) during the 6 months prior to inclusion were randomized to receive pasireotide-LAR 60 mg ( n = 10) or placebo ( n = 12) every 28 days for 6 months. Patients were then followed for an additional 6 months after stopping treatment. Results: The pasireotide-LAR and placebo groups were equivalent for age, sex, comorbidities and transfusion requirement during the reference period (median 13 and 9.5 pRBCs). A 50 and 83% success rate (success defined as a decrease of at least 30% of transfused pRBCs) was observed in the pasireotide-LAR arm in the Intent to Treat (ITT) and per protocol (PP) analysis respectively. The need for transfusion during the intervention period was 3 pRBC units in the pasireotide-LAR group (range 0–26) and 11.5 pRBC units in the placebo group (range 0–23). Overall, three cases with glycemic control impairment were observed in the pasireotide-LAR group including one de novo diabetes. Conclusion: This double-blinded noncomparative randomized phase II study suggests, for the first time, the effectiveness of pasireotide-LAR 60 mg every 28 days to decrease the transfusion requirement in patients with recurrent bleeding due to GIADs.